2009
DOI: 10.5194/nhess-9-469-2009
|View full text |Cite
|
Sign up to set email alerts
|

Integrated database for rapid mass movements in Norway

Abstract: Abstract. Rapid gravitational slope mass movements include all kinds of short term relocation of geological material, snow or ice. Traditionally, information about such events is collected separately in different databases covering selected geographical regions and types of movement. In Norway the terrain is susceptible to all types of rapid gravitational slope mass movements ranging from single rocks hitting roads and houses to large snow avalanches and rock slides where entire mountainsides collapse into fjo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 7 publications
0
37
1
Order By: Relevance
“…The study also showed that in Uganda, most people are injured or killed outside and not at their place of residence. This diverges from the data describing Norwegian quick clay landslides, where loss of life occurred most frequently in the person's place of residence (Jaedicke et al 2009). Zhang and Zhang (2014) examined factors involved with human flight behavior related to rapid landslides along roads in China.…”
Section: Factors Affecting Susceptibility (S F )contrasting
confidence: 42%
See 3 more Smart Citations
“…The study also showed that in Uganda, most people are injured or killed outside and not at their place of residence. This diverges from the data describing Norwegian quick clay landslides, where loss of life occurred most frequently in the person's place of residence (Jaedicke et al 2009). Zhang and Zhang (2014) examined factors involved with human flight behavior related to rapid landslides along roads in China.…”
Section: Factors Affecting Susceptibility (S F )contrasting
confidence: 42%
“…Considering the Nordic countries, approximately 2000 people have been killed by all kinds of landslides in Norway (Jaedicke et al 2009) during the last 150 years. No such compilation has been performed for Sweden, but since 1950, at least 10 people have lost their lives, and 160 were injured as a result of landslides (MSB 2016).…”
Section: Landslide Characteristics and Methods For Quantification Expmentioning
confidence: 99%
See 2 more Smart Citations
“…Upwelling will also bring low-O 2 , high-CO 2 water onto the shelf and upper slope (Bakun, 1990;Feely et al, 2008;Bakun et al, 2010;Sydeman et al, 2014;Wang et al, 2015). Increased levels of precipitation on land will also alter terrestrial inputs, including sediments and organic debris, nutrients, and contaminants (Jaedicke et al, 2009;Caroletti and Barstad, 2010) that may smother seafloor sediments, and alter the trophic ecology of deep-sea habitats situated close to land Wing, 2007, McLeod et al, 2010).…”
Section: Seafloor Ecosystem Changes Under Future Climate Change Scenamentioning
confidence: 99%